Ice surface morphology and flow on Malaspina Glacier, Alaska: Implications for regional tectonics in the Saint Elias orogen. Issue 4 (17th April 2014) - Cotton, Michelle M.; Bruhn, Ronald L.; Sauber, Jeanne; Burgess, Evan; Forster, Richard R.
Abstract The Saint Elias Mountains in southern Alaska are located at a structural syntaxis where the coastal thrust and fold belt of the Fairweather plate boundary intersects thrust faults and folds generated by collision of the Yakutat Terrane. The axial trace of this syntaxis extends southeastward out of the Saint Elias Mountains and beneath Malaspina Glacier where it is hidden from view and cannot be mapped using conventional methods. Here we examine the surface morphology and flow patterns of Malaspina Glacier to infer characteristics of the bedrock topography and organization of the syntaxis. Faults and folds beneath the eastern part of the glacier trend northwest and reflect dextral transpression near the terminus of the Fairweather fault system. Those beneath the western part of the glacier trend northeast and accommodate folding and thrust faulting during collision and accretion of the Yakutat Terrane. Mapping the location and geometry of the structural syntaxis provides important constraints on spatial variations in seismicity, fault kinematics, and crustal shortening beneath Malaspina Glacier, as well as the position of the collisional deformation front within the Yakutat Terrane. We also speculate that the geometrical complexity of intersecting faults within the syntaxis formed a barrier to rupture propagation during two regional Mw 8.1 earthquakes in September 1899.